Financing sustainable forest management: report of the International Workshop of Experts, 22-25 January 2001, Oslo, Norway - Chipeta, M.E.; Joshi, M. (Center for International Forestry Research, 2001)
This report summarizes the outcome of the workshop and consists of three parts. Part 1 highlights that were issued at the end of the workshop. Funding is not the sole constraints to investment in sustainable forest management (SFM) in developing countries. It also requires an enabling environment at the international level. A continuing decline in commodity prices at the international level has prevented the forest sector from yielding adequate financial surpluses that could be reinvestated into sustainable forest management. Greater investment is needed from private sector, public sector, and official development assistance. Means of promoting SFM financing: investment promotion entity (IPE), global forest fund (GFF) and other international financial resources were discussed. Part 2 provides summaries of the papers prepared for the workshop. Part 3 contains the speeches and agenda of the workshop, a list of relevant documents and a list of participants. Proceedings of this workshop is published only in a CD-ROM and consists of the highlights and the full set of papers for the workshop.